Fundamentals of Electrical Engineering I - Johnson, Don (Open textbook library., 2014)
The course focuses on the creation, manipulation, transmission, and reception of information by electronic means. Elementary signal theory; time- and frequency-domain analysis; Sampling Theorem. Digital information theory; digital transmission of analog signals; error-correcting codes.